The effect of injectable platelet-rich fibrin and platelet-rich fibrin in regenerative endodontics: a comparative in vitro study - Jing PAN; Linjuan LUO; Zhen JIANG; Haiyan HUANG; Beizhan JIANG (University of São Paulo, 2024)
Abstract Objective To explore the feasibility of injectable platelet-rich fibrin (i-PRF) in regenerative endodontics by comparing the effect of i-PRF and platelet-rich fibrin (PRF) on the biological behavior and angiogenesis of human stem cells from the apical papilla (SCAPs). Methodology i-PRF and PRF were obtained from venous blood by two different centrifugation methods, followed by hematoxylin-eosin (HE) staining and scanning electron microscopy (SEM). Enzyme-linked immunosorbent assay (ELISA) was conducted to quantify the growth factors. SCAPs were cultured with different concentrations of i-PRF extract (i-PRFe) and PRF extract (PRFe), and the optimal concentrations were selected using the Cell Counting Kit-8 (CCK-8) assay. The cell proliferation and migration potentials of SCAPs were then observed using the CCK-8 and Transwell assays. Mineralization ability was detected by alizarin red staining (ARS), and angiogenesis ability was detected by tube formation assay. Real-time quantitative polymerase chain reaction (RT-qPCR) was performed to evaluate the expression of genes related to mineralization and angiogenesis. The data were subjected to statistical analysis. Results i-PRF and PRF showed a similar three-dimensional fibrin structure, while i-PRF released a higher concentration of growth factors than PRF ( P <.05). 1/4× i-PRFe and 1/4× PRFe were selected as the optimal concentrations. The cell proliferation rate of the i-PRFe group was higher than that of the PRFe group ( P <.05), while no statistical difference was observed between them in terms of cell mitigation ( P >.05). More importantly, our results showed that i-PRFe had a stronger effect on SCAPs than PRFe in facilitating mineralization and angiogenesis, with the consistent result of RT-qPCR ( P <.05). Conclusion This study revealed that i-PRF released a higher concentration of growth factors and was superior to PRF in promoting proliferation, mineralization and angiogenesis of SCAPs, which indicates that i-PRF could be a promising biological scaffold for application in pulp regeneration.